2023
DOI: 10.1037/trm0000393
|View full text |Cite
|
Sign up to set email alerts
|

The role of trauma, psychological therapy, and trauma appraisals in predicting posttraumatic growth.

Abstract: This study examined the relationship between posttraumatic stress and posttraumatic growth (PTG), as well as the role of wider trauma-related factors, demographic characteristics, and trauma appraisals in the development of PTG. This cross-sectional study used a quantitative survey methodology. An opportunity sample of 85 trauma-exposed adults (56 male and 28 female) with a mean age of 48.26 years was recruited from psychological support services in Northern Ireland. Participants had experienced an average of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Another limitation is that the study did not examine a range of factors previously found to correlate with PTG, such as coping flexibility, coping self-efficacy, appraisals, anger, posttraumatic depreciation, event centrality, hope, optimism, or significant others’ PTG (De Roon-Cassini et al, 2010; Gleeson et al, 2022; Hafstad et al, 2010; Henson et al, 2021; Kunz et al, 2018; Long et al, 2020; Michélsen et al, 2017; Zoellner et al, 2011). These factors may warrant consideration in future longitudinal PTG research.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that the study did not examine a range of factors previously found to correlate with PTG, such as coping flexibility, coping self-efficacy, appraisals, anger, posttraumatic depreciation, event centrality, hope, optimism, or significant others’ PTG (De Roon-Cassini et al, 2010; Gleeson et al, 2022; Hafstad et al, 2010; Henson et al, 2021; Kunz et al, 2018; Long et al, 2020; Michélsen et al, 2017; Zoellner et al, 2011). These factors may warrant consideration in future longitudinal PTG research.…”
Section: Discussionmentioning
confidence: 99%